Implications of narrow crop row spacing in managing weeds in mungbean (Vigna radiata). (May 2017) - Chauhan, Bhagirath Singh; Florentine, Singarayer Kumardas; Ferguson, J. Connor; Chechetto, Rodolfo G.
Abstract: The mungbean production area is increasing in Australia due to increasing demand for the grain in Asian countries. However, the mungbean crop is generally grown with wide row spacing, and therefore, it is prone to heavy weed infestation which has a significant impact on the mungbean grain yield. Experiments were conducted in 2015 and 2016 to determine the row-spacing impact on crop yield and weed growth for mungbean grown in 25, 50, and 75 cm space rows. Row spacing did not affect weed biomass and mungbean grain yield when weeds were allowed to grow from crop sowing to maturity. However, narrower row spacing (25 and 50 cm) had lower weed biomass and higher grain yield when weeds were allowed to grow beyond 3 and 6 weeks after planting (WAP). Mungbean grown at 25 and 50 cm rows had 60–70% and 70–92% less weed biomass than the mungbean grown at 75 cm rows for the weeds grown beyond 3 and 6 WAP, respectively. In weed-free conditions, too, mungbean grain yields were greater in narrow rows than in wider rows. Weeds grown beyond 6 WAP did not affect grain yield of 25 and 50 cm rows but reduced mungbean yield with 75 cm rows. The practical implication of this study is that narrowing row spacing in mungbean could lead to reduced weed growth and seed production and increased crop yield. Highlights: Mungbean crop is generally grown with wide row spacing. So, it is prone to heavy weed infestation. Narrower row spacing had lower weed biomass and higher grain yield. Narrowing row spacing in mungbean could lead to reduced weed growth and seed production. Narrowing row spacing could increased crop yield.